Identification of a new set of cell cycle-regulatory genes that regulate S-phase transcription of histone genes in Saccharomyces cerevisiae. - Xu, H (1992)
Histone mRNA synthesis is tightly regulated to S phase of the yeast Saccharomyces cerevisiae cell cycle as a result of transcriptional and posttranscriptional controls. Moreover, histone gene transcription decreases rapidly if DNA replication is inhibited by hydroxyurea or if cells are arrested in G1 by the mating pheromone alpha-factor. To identify the transcriptional controls responsible for cycle-specific histone mRNA synthesis, we have developed a selection for mutations which disrupt this process. Using this approach, we have isolated five mutants (hpc1, hpc2, hpc3, hpc4, and hpc5) in which cell cycle regulation of histone gene transcription is altered. All of these mutations are recessive and belong to separate complementation groups. Of these, only one (hpc1) falls in one of the three complementation groups identified previously by other means (M. A. Osley and D. Lycan, Mol. Cell. Biol. 7:4204-4210, 1987), indicating that at least seven different genes are involved in the cell cycle-specific regulation of histone gene transcription. hpc4 is unique in that derepression occurs only in the presence of hydroxyurea but not alpha-factor, suggesting that at least one of the regulatory factors is specific to histone gene transcription after DNA replication is blocked. One of the hpc mutations (hpc2) suppresses delta insertion mutations in the HIS4 and LYS2 loci. This effect allowed the cloning and sequence analysis of HPC2, which encodes a 67.5-kDa, highly charged basic protein.